The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1998
DOI: 10.1128/jvi.72.7.5559-5564.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Epstein-Barr Virus (EBV) gN Homolog BLRF1 Encodes a 15-Kilodalton Glycoprotein That Cannot Be Authentically Processed unless It Is Coexpressed with the EBV gM Homolog BBRF3

Abstract: The Epstein-Barr virus (EBV) homolog of the conserved herpesvirus glycoprotein gN is predicted to be encoded by the BLRF1 open reading frame (ORF). Antipeptide antibody to a sequence corresponding to residues in the predicted BLRF1 ORF immunoprecipitated a doublet of approximately 8 kDa from cells expressing the BLRF1 ORF as a recombinant protein. In addition, four glycosylated proteins of 113, 84, 48, and 15 kDa could be immunoprecipitated from virus-producing cells by the same antibody. The 15-kDa species wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The meaning of this interaction is not yet fully understood but it is important for the transport of gM into the trans-Golgi-network, and only the mature gM is fully functional . Similar complex formations between gM and the respective UL49?5 products have been described for PRV, bovine herpesvirus 1 (BoHV-1), Epstein-Barr virus and human cytomegalovirus (Jöns et al, 1998;Lake et al, 1998;Wu et al, 1998;Mach et al, 2000). In most herpesviruses analysed to date, deleting gM does not result in a marked phenotype in vitro, causing its specific function still to be a matter of discussion.…”
Section: Introductionmentioning
confidence: 58%
“…The meaning of this interaction is not yet fully understood but it is important for the transport of gM into the trans-Golgi-network, and only the mature gM is fully functional . Similar complex formations between gM and the respective UL49?5 products have been described for PRV, bovine herpesvirus 1 (BoHV-1), Epstein-Barr virus and human cytomegalovirus (Jöns et al, 1998;Lake et al, 1998;Wu et al, 1998;Mach et al, 2000). In most herpesviruses analysed to date, deleting gM does not result in a marked phenotype in vitro, causing its specific function still to be a matter of discussion.…”
Section: Introductionmentioning
confidence: 58%
“…Encoded by the UL10 gene in HSV-1, gM is a type III membrane protein with eight predicted transmembrane domains (Baines & Roizman, 1993;MacLean et al, 1991MacLean et al, , 1993. In several herpesviruses, gM has been shown to form a disulphide-linked complex with glycoprotein N (gN), although an interaction between HSV-1 gM and gN has yet to be demonstrated (Jöns et al, 1998;Koyano et al, 2003;Lake et al, 1998;Lipiń ska et al, 2006;Mach et al, 2000;Rudolph et al, 2002;Wu et al, 1998). It has been reported that gM is non-essential for the replication of many alphaherpesviruses, including HSV-1 (Baines & Roizman, 1991;MacLean et al, 1993), pseudorabies virus (PRV) (Dijkstra et al, 1996), bovine herpesvirus type 1 (König et al, 2002), varicella-zoster virus (Yamagishi et al, 2008), infectious laryngotracheitis virus (Fuchs & Mettenleiter, 1999), equine herpesvirus type 1 (EHV-1) (Osterrieder et al, 1996) and EHV type 4 (Ziegler et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…10-to 100-folddecreased virus titers. gM forms a complex with the product of the UL49.5 homologous genes, as shown for PrV (21), bovine herpesvirus 1 (53), and Epstein-Barr Virus (27). Since the UL49.5 products are glycosylated in PrV and Epstein-Barr virus, they have been designated gN.…”
mentioning
confidence: 99%